Occlusal Outcome of Orthodontic Treatment for Patients With Complete Cleft Lip and Palate. (January 2022) - Stonehouse-Smith, Daniel; Rahman, Aida N.A. Abd; Mooney, Jeanette; Bellardie, Haydn
Aim: To assess occlusal outcomes of orthodontic treatment for patients with complete cleft lip and palate. Design: Retrospective assessment using the Peer Assessment Rating (PAR) index. Setting: Consecutive patients treated by one consultant orthodontist at a tertiary care cleft center. Participants: One hundred twenty-seven patients with either complete unilateral cleft lip and palate (UCLP) or bilateral cleft lip and palate (BCLP) consecutively treated with fixed appliances. Intervention: Fixed orthodontic appliance treatment and orthognathic surgery when required. Outcomes: The PAR index assessment was carried out by a calibrated-independent assessor. Treatment duration, the number of patient visits, and data on dental anomalies were drawn from patient records and radiographs. Results: One hundred two patients' study models were assessed after exclusions. Mean start PAR score for UCLP (n = 71) was 43.9 (95% CI, 41.2-46.6, SD 11.5), with a mean score reduction of 84.3% (95% CI, 81.9-86.7, SD 10.1). The UCLP mean treatment time was 23.7 months with 20.1 appointments. Mean start PAR score for BCLP (n = 31) was 43.4 (95% CI, 39.2-47.6, SD 11.4), with a mean score reduction of 80.9% (95% CI, 76.3-85.5, SD 12.5). The BCLP mean treatment time was 27.8 months with 20.5 appointments. Conclusion: These results compare well with other outcome reports, including those for patients without a cleft, and reflect the standard of care provided by an experienced cleft orthodontist. As with high-volume surgeons, orthodontic treatment for this high need group is favorable when provided by a high-volume orthodontist. These findings may be used for comparative audit with similar units providing cleft care.